Developing Multi-Copy Chromosomal Integration Strategies for Heterologous Biosynthesis of Caffeic Acid in Saccharomyces cerevisiae - Qi, Hang; Yu, Long; Li, Yuanzi; Cai, Miao; He, Jiaze; Liu, Jiayu; Hao, Luyao; Xu, Haijin; Qiao, Mingqiang (Frontiers in Microbiology, 2022)
Caffeic acid, a plant-sourced phenolic compound, has a variety of biological activities, such as antioxidant and antimicrobial properties. The caffeic acid biosynthetic pathway was initially constructed in S. cerevisiae, using codon-optimized TAL (coTAL, encoding tyrosine ammonia lyase) from Rhodobacter capsulatus, coC3H (encoding p-coumaric acid 3-hydroxylase) and coCPR1 (encoding cytochrome P450 reductase 1) from Arabidopsis thaliana in 2µ multi-copy plasmids to produce caffeic acid from glucose. Then, integrated expression of coTAL via delta integration with the POT1 gene (encoding triose phosphate isomerase) as selection marker and episomal expression of coC3H, coCPR1 using the episomal plasmid pLC-c3 were combined, and caffeic acid production was proved to be improved. Next, the delta and rDNA multi-copy integration methods were applied to integrate the genes coC3H and coCPR1 into the chromosome of high p-coumaric acid yielding strain QT3-20. The strain D9 constructed via delta integration outperformed the other strains, leading to 50-fold increased caffeic acid production in optimized rich media compared with the initial construct. The intercomparison between three alternative multi-copy strategies for de novo synthesis of caffeic acid in S. cerevisiae suggested that delta-integration was effective in improving caffeic acid productivity, providing a promising strategy for the production of valuable bio-based chemicals in recombinant S. cerevisiae.